Review of NGO performance research published in academic journals between 1996 and 2008 - Roselyn Kareithi; Crick Lund (South African Journal of Science)
Globally, literature on the performance of development non-governmental organisations (NGOs) has increased. However, little is known regarding the distinctive characteristics of academic articles on factors influencing NGO performance. In a recent systematic review of research, published in English-language academic journals between 1996 and 2008, factors influencing NGO performance were investigated. From the 31 journal articles that met the inclusion criteria, this study examined the salient characteristics of NGO performance research in terms of, (1) the number of publications, (2) publication outlets (journals and journal cluster), (3) author collaboration (sole or joint authors), (4) author affiliation, (5) study location, (6) study period, (7) study topics and (8) method and sources of information. Findings showed a steady increase in the number of articles, published in a wide array of journals with over half of the articles published in development studies journals. Of the 31 articles, 21 were sole authored. Data were mainly sought from NGO directors, programme staff and donors; comparatively fewer studies collected data from beneficiaries. Studies were mainly conducted in developing countries, whilst most authors were affiliated to institutions in developed countries. Of the 13 authors who conducted studies in Africa only 3 were affiliated to an institution in Africa. This study confirmed the continued need for increased research on factors influencing NGO performance; revealed the low seeking of beneficiaries' perspectives in NGO performance research despite the rhetoric of participatory development; and revealed the low number of published researchers in Africa and minimal collaborative efforts between "Northern" and "Southern" researchers in this field.